Спільна діяльність адвокатури і громадськості в захисті прав і свобод людини - Бандурка, С. С.; Bandurka, S. S. (Українська поліцеїстика: теорія, законодавство, практика. - 2024. - № 2(10). - С. 68-75, 2024)
У статті досліджено форми і методи взаємодії адвокатури і громадськості в системі захисту прав і свобод людини. Схарактеризовано особливості такої взаємодії в умовах воєнного стану, в якому перебуває Україна у зв’язку з повномасштабною агресією російської федерації. Правовий режим воєнного стану зумовив зміни в характері взаємодії адвокатури і громадських об’єднань. Аргументовано, що адвокатура в системі зв’язків з громадськістю виступає як інститут громадянського суспільства, послуг якої в тій чи іншій формі потребують усі інші як державні, так і недержавні суб’єкти права.

The article examines the forms and methods of interaction between the legal profession and public associations in the system of protection of human rights and freedoms. The peculiarities of such interaction in the conditions of martial law, in which Ukraine enters due to the full-scale aggression of the Russian Federation, are characterized. Emphasis is placed on the changes in the social life of Ukraine, which caused changes in the nature of interaction between the legal profession and public associations. Forms and methods of interaction of the legal profession with public associations in the field of protection of human rights and freedoms are conditioned by the types of legal activity and professional rights of lawyers provided for in the Law of Ukraine "On Advocacy and Legal Activities" and taking into account the requirements of the Law of Ukraine "On the Legal Regime of Martial Law". It is argued that the legal profession in the system of relations with public associations acts as a central, main element, the services of which are needed in one form or another by all other non-state legal subjects organized in public organizations. The Bar is able to provide legal assistance to all public associations in need of legal assistance, without expecting any reciprocation from them. Figuratively speaking, the advocacy can unite without third-party organizations, and they cannot do without the advocacy in certain situations. No public organization has such wide powers in the field of protection of human rights and freedoms as the bar, which is also a public organization that functions as an integral part of the state mechanism in the field of administration of justice.

В статье исследованы формы и методы взаимодействия адвокатуры и общественности в системе защиты прав и свобод человека. Охарактеризованы особенности такого взаимодействия в условиях военного положения, в котором находится Украина в связи с полномасштабной агрессией российской федерации. Правовой режим военного положения обусловил изменения в характере взаимодействия адвокатуры и общественных объединений. Аргументировано, что адвокатура в системе связей с общественностью выступает как институт гражданского общества, в услугах которой в той или иной форме нуждаются все другие как государственные, так и негосударственные субъекты права.
Joint activities of advocacy and society in protection of human rights and freedoms
Keywords: адвокатура; громадськість; захист прав і свобод людини; взаємодія; система; advocacy; public associations; protection of human rights and freedoms; interaction; system; общественность; защита прав и свобод человека; взаимодействие